Pengaruh Karakteristik Perusahaan, Kinerja Keuangan, Dan Corporate Governance Terhadap Sustainability Rreporting - Bakti Maulana Ikhsan; Rita Wijayanti (Duconomics Sci-meet (Education & Economics Science Meet), 2021)
This study aims to analyze and examine the effect of fim’s characteristics, financial performance, and corporate governance on sustainability reporting. The research method uses a quantitative approach. The population in this study are State-Owned Enterprises (BUMN) listed on the Indonesia Stock Exchange (IDX) for the 2014-2019 period. This study uses purposive sampling method and obtained 13 state-owned companies with 78 research samples for six years of observation. The data were tested using multiple linear regression method. The results of this study indicate that the variables of firm’s characteristics proxied by leverage, and corporate governance as proxied by independent commissioners and directors have a significant effect on sustainability reporting. While the variables of firm’s characteristics which are proxied by firm size and liquidity, financial performance variables which are proxied by profitability, and corporate governance variables which are proxied by institutional share ownership, and the audit committee have no significant effect on sustainability reporting. The results of this study can be used for decision making of various parties.